Les musiciens gnawa à Bruxelles : une reconfiguration culturelle - Hélène Sechehaye; Stéphanie Weisser (Brussels Studies)
This article examines the Gnawa musical practices in Brussels through an ethnomusicological approach. The Gnawa belong to a community originating in Morocco, and have integrated new elements into their practices, which could be explained by their relocation abroad. Furthermore, the comparison with the situation in other cities allows us to assume that the situation in Brussels has a unique character. There have been changes in the methods of learning this musical practice, women now mix with men not only in secular but also ritual musical practice, and there has been a diversification of performance contexts. This has prompted Gnawa musicians to learn other Moroccan musical styles, which they use as inspiration for their Gnawa repertoire, in theory closed to the integration of outside elements. Far from deploring a hypothetical loss of authenticity due to their migration, the Gnawa in Brussels have redefined their musical practices and their methods of operation, by adapting them to their new place of residence. In so doing, they continually reshape their identity, which allows them to be part of a very specific cultural and social heritage while exploring new territories.